1993
DOI: 10.1038/361657a0
|View full text |Cite
|
Sign up to set email alerts
|

Two nuclear signalling pathways for vitamin D

Abstract: The dihydroxylated form of vitamin D3 (1,25-dihydroxy-D3)mediates a biological response by binding to intracellular receptors which belong to the steroid receptor superfamily. These receptors act as ligand-dependent transcription factors that bind to specific DNA sequences (reviewed in refs 6-9). We have identified two classes of vitamin D response elements that are activated either by the vitamin D receptor (VDR) alone or by heterodimers of VDR and the retinoid-X receptor-alpha (RXR-alpha). The motif GGGTGA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
280
3

Year Published

1994
1994
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 510 publications
(293 citation statements)
references
References 30 publications
10
280
3
Order By: Relevance
“…Similar to our previous observations, overexpression of menin increased ligand-induced transcription to almost threefold, depending on the amount of menin that was co-transfected ( Figure 2A) (Dreijerink et al, 2006). VDR binds to its response elements as a heterodimer with the retinoid X receptor (RXR) (Carlberg et al, 1993). To determine if menin can also interact with RXR, additional luciferase experiments were performed.…”
Section: Menin Can Co-activate Vdr-mediated Transcription Via a Direcsupporting
confidence: 81%
“…Similar to our previous observations, overexpression of menin increased ligand-induced transcription to almost threefold, depending on the amount of menin that was co-transfected ( Figure 2A) (Dreijerink et al, 2006). VDR binds to its response elements as a heterodimer with the retinoid X receptor (RXR) (Carlberg et al, 1993). To determine if menin can also interact with RXR, additional luciferase experiments were performed.…”
Section: Menin Can Co-activate Vdr-mediated Transcription Via a Direcsupporting
confidence: 81%
“…For example, it was reported that VDR expressed in baculovirus and yeast was unable to interact directly with VDREs ; these results were interpreted to mean that VDR cannot form homodimers [25,27]. In a study that used gel-shift assays, purified VDRs were shown to bind to the osteopontin VDRE in the absence of RXR ; however, RXR was required for binding to osteoclasin VDRE [35], whereas opposite results were obtained in a study in which VDR translated in itro was used [36]. The conflicting results are likely to be due to differences in sample quality and purity as well as in methodology.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that RXR is silent in the RXR/VDR heterodimers on binding to the DR3 (direct repeats spaced by 3 nucleotides) response element [25]. However, additive or synergistic transcriptional activation has been observed when RXR/VDR heterodimers bind to particular response elements (osteopontin vitamin D response element and DR3) in different cells (human breast cancer cell line MCF-7 and Drosophila SL-3 cells) [30], suggesting that the role of RXR in VDR-mediated transactivation is gene-and cell line-specific. It has been demonstrated that RXR is an essential partner of VDR and actively participates in VDR-dependent gene expression [31].…”
Section: Discussionmentioning
confidence: 99%